The influence of the brain-based learning (BBL) model assisted by multimedia phet simulation on critical thinking ability - An Nisaa', Mutiara; Karsono, Karsono; Salimi, Moh (Jurnal JPSD (Jurnal Pendidikan Sekolah Dasar), 2025)
Mathematics learning in elementary schools is still dominated by conventional methods that do not foster the development of critical thinking skills. This challenge is relevant to 21st-century learning and the Independent Curriculum, which demands the integration of technology and high-level thinking skills. This research aims to analyze the effect of Brain-Based Learning (BBL) supported by PhET Simulations on the critical thinking abilities of fifth-grade students in Magelang City. The research approach uses a quasi-experimental design with a nonequivalent control group. The research instrument is an essay test to measure critical thinking abilities. The results of the analysis show that the BBL model assisted by PhET Simulation provides a significant improvement in critical thinking abilities. Data testing uses the t-test and N-Gain to prove the hypothesis. The t-test produces a significance value of 0.00 < 0.05, indicating a significant effect of using BBL assisted by the PhET Simulation. This finding is strengthened by the average N-Gain value of 0.5002, which falls within the medium category, indicating that brain-based work learning is quite effective in improving students' critical thinking abilities. Integration of BBL and PhET Simulations proved effective in supporting 21st-century skills. Implementing this model can provide learning experiences that support optimal brain function through technology, making it relevant for developing 21st-century skills.